CONCEPT AND PRINCIPLES OF PERIODIC TRAINING IN GYMNASTICS (Universal International Scientific Journal, 2026)
This scientific article presents theoretical and practical recommendations on the longterm concept of training highly qualified gymnasts, based on the unity of organizational and programmethodological foundations, material and technical support of the training process, systematic andintegrated use of special means and methods, as well as pedagogical and medical-biological control
Keywords: physical development; stage-based approach; current control